THE PROVISION ON SEAGRASS ECOSYSTEM SERVICES TO SMALL-SCALE FISHERIES ACTIVITY IN EASTERN COASTAL OF BINTAN ISLAND, RIAU ISLANDS - M. Nur Arkham (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2018)
The seagrass ecosystem has the same role as other ecosystem in improving coastal community fishery business. The purpose of this study is to assess the provision of seagrass ecosystem services to small fishing activities in the study sites. The research was conducted in Malang Village Meeting and Berakit from September to November 2014. Spatial distribution of fish species resources and small fishing catchment areas at study sites were located near the coast in each study village. The activity of catching small fishermen by utilizing the existence of seagrass ecosystem is reflected from the resources of fish species that are obtained and marketed to meet their needs. Fish community structure associated with seagrass from small fisherman catch in Malang Village Meeting based on index value of diversity (H ') and uniformity (E) of 2.58 and 0.93 higher than that of Desa Berakit that is 1.77 and 0.65. This value indicates that the keaganagaman in Malang Village is Medium and the community is in stable condition. While in the village of Berakit shows low diversity and community in unstable conditions. While the value of dominance index (C) of each village is low with the value of each village of 0.09 and 0.31. Keywords: seagrass ecosystem services, small-scale fisheries, and Eastern Coastal of Bintan